SHAPE-SSA: a region-specific Soil Health Assessment Protocol and Evaluation for Sub-Saharan Africa - Moges Kidane Biru; Nunes, Marcio R.; Mackowiak, Cheryl L.; Biratu, Gizachew Kebede; Mohkam-Singh; Niguse Bekele Dirbaba; Elias, Eyasu; Sida, Tesfaye Shiferaw (2025)
Tropical croplands sit on heavily weathered soils where their potential to provide soil functions such as carbon storage is significantly influenced by climate and mineral composition. However, the gap between these biophysical potential and effect of management is not well quantified. Most soil health assessment frameworks were developed for temperate regions and often fail to reflect the ecological variety and pedogenic constraints of tropical soils. To fill this gap, we developed the Soil Health Assessment Protocol and Evaluation framework for SSA (SHAPE-SSA). We link inherent soil and climate variables with management responsive indicators in hierarchical Bayesian models that quantify uncertainty and estimate peer-group distributions. In this first application, we focus on soil organic carbon (SOC) as a key indicator of soil health, drawing on more than 28,000 georeferenced samples. From these peer distributions we define context-aware, percentile-based benchmarks that evaluate soils relative to their ecological potential rather than fixed thresholds. The resulting opportunity gap metric distinguishes between limits set by soil formation processes and climate, and deficiencies that arise from management practices. Our analysis shows that long-term weathering and moisture regimes restrict maximum SOC in these tropical highlands, while management determines how close individual fields come to those limits. These factors provide field scale information for realistic soil health gains in intensively farmed tropical systems.